Emerging nitrogenous disinfection byproducts: Transformation of the antidiabetic drug metformin during chlorine disinfection of water. (1st August 2015) - Armbruster, Dominic; Happel, Oliver; Scheurer, Marco; Harms, Klaus; Schmidt, Torsten C.; Brauch, Heinz-Jürgen
Abstract: As an environmental contaminant of anthropogenic origin metformin is present in the high ng/L- up to the low μg/L-range in most surface waters. Residues of metformin may lead to the formation of disinfection by-products during chlorine disinfection, when these waters are used for drinking water production. Investigations on the underlying chemical processes occurring during treatment of metformin with sodium hypochlorite in aqueous medium led to the discovery of two hitherto unknown transformation products. Both substances were isolated and characterized by HPLC-DAD, GC-MS, HPLC-ESI-TOF, 1 H-NMR and single-crystal X-ray structure determination. The immediate major chlorination product is a cyclic dehydro-1, 2, 4-triazole-derivate of intense y ellow color (Y ; C4 H6 ClN5 ). It is a solid chlorimine of limited stability. Rapid formation was observed between 10 °C and 30 °C, as well as between pH 3 and pH 11, in both ultrapure and tap water, even at trace quantities of reactants (ng/L-range for metformin, mg/L-range for free chlorine). While Y is degraded within a few hours to days in the presence of light, elevated temperature, organic solvents and matrix constituents within tap water, a secondary degradation product was discovered, which is stable and c olorless (C ; C4 H6 ClN3 ). This chloroorganic nitrile has a low photolysis rate in ambient day light, while being resistant to heat and not readily degraded in the presence of organic solvents or in the tap water matrix. In addition, the formation of ammonia, dimethylamine and N, N -dimethylguanidine was verified by cation exchange chromatography. Graphical abstract: Highlights: Two hitherto unknown chlorine transformation products of metformin were discovered. Metformin is primarily converted to a reactive chlorimine Y of intense yellow color. Trace quantities of Y rapidly decompose to a refractory chloroorganic nitrile C . A detection limit below 0.05 ng/L was determined for C using SPE and HPLC-MS/MS. C was found after chlorination of tap water containing traces of metformin.